Changes in bacterial community structure and quality characteristics during fermentation of stinky variegated carp (Aristichthys nobilis). Issue 9 (31st March 2022) - Pang, Chunxia; Li, Yi; Yu, Renying; Wang, Junhao; Li, Xuerui; Chen, Yuru; Yu, Lijuan; Luo, Haibo
Abstract: Bacterial metabolism greatly affects the quality and flavor of traditional, low‐salt fermented fish. We assessed changes in the bacterial community structure and quality characteristics of "stinky" variegated carp ( Aristichthys nobilis ) during fermentation at 20°C. The total viable count (TVC), firmness, chewiness, tackiness, total volatile base nitrogen (TVB‐N) and thiobarbituric acid‐reactive substance (TBARS) levels, and relative peak area of volatile compounds significantly ( p  < .05) increased, while the pH, weight, and elasticity dramatically decreased, during fermentation. The total free amino acid (FAA) content decreased early during fermentation (from 0–2 d) and then significantly ( p  < .05) increased (from 3–5 d). The levels of flavorful AAs (aspartic acid, glutamate, phenylalanine, tyrosine, alanine, and glycine) increased markedly after 4 d of fermentation. Solid‐phase microextraction‐gas chromatography–mass spectrometry (SPME‐GC–MS) revealed that the levels of ketones, ethers, and nitrogenous compounds increased significantly ( p  < .05) during fermentation. Illumina MiSeq sequencing identified Plesiomonas as the dominant bacterial genus during fermentation, followed by Aeromonas, Cetobacterium, Vibrio, and Hathewaya . These bacteria may contribute to the flavor and aroma of stinky variegated carp. The association between bacterial succession and the flavor and taste of stinky fish was also discussed. Practical applications: Variegated carp could be processed to create stinky fish. In this study, bacterial community structure and quality characteristics analysis were assessed. FAAs and volatile compounds related to flavor and aroma were found. A potential starter culture that could improve the quality of stinky variegated carp was identified. Our findings provide a theoretical basis for the industrial production of fermented stinky fish.